Caribbean agriculture moves forward - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
With the move towards free trade and globalization of markets, the economic survival and development of many Caribbeancountries may depend on their membership of Caricom (Caribbean Common Market) - a regional trading bloc of around sixmillion...